Idarucizumab for Reversing Dabigatran-Induced Anticoagulation: A Systematic Review. (May 2018) - Thibault, Nathan; Morrill, Amanda M.; Willett, Kristine C.
Abstract : Background: The approval of the oral direct thrombin inhibitor, dabigatran etexilate, gave patients an alternative to oral anticoagulation with warfarin. Like all anticoagulants, the primary adverse event (AE) associated with dabigatran is bleeding. Until the FDA approval of idarucizumab, there had been no reversal agent for dabigatran-induced anticoagulation in patients with life-threatening or uncontrollable bleeding, or those requiring emergent procedures. Areas of Uncertainty: The primary purpose of this review is to summarize the safety and efficacy of idarucizumab, a monoclonal antibody fragment, and its use as a reversal agent for dabigatran. Data Sources: A literature search was conducted through MEDLINE (1946 to November week 1 2015) and Embase (1980–2015 week 46) using the search term idarucizumab.Clinicaltrials.gov was consulted for a comprehensive list of ongoing and completed studies. Additional studies were identified through bibliographical citations. Clinical trials in animals and humans published in English evaluating the safety and efficacy of idarucizumab for reversal of anticoagulant treatment with dabigatran were included for review. Results: Idarucizumab has been shown to significantly reverse the anticoagulant effects of dabigatran in both healthy volunteers and patients requiring a reversal agent because of either overt bleeding or an emergency surgery or invasive procedure. The most common AEs were headache, nasopharyngitis, back pain, skin irritation, hypokalemia, delirium, constipation, pyrexia, and pneumonia. Deaths reported in idarucizumab studies were attributed to either the index event or a preexisting comorbidity. Most adverse effects were minor, but 21 serious AEs have been reported in the published data including thrombotic events. Conclusions: Given the increased use of direct oral anticoagulants, such as dabigatran, a need for specific reversal agents exists. Idarucizumab has been shown to be safe and effective in the reversal of dabigatran-induced anticoagulation in patients requiring emergent or urgent surgery or in patients with severe bleeding.